A PROBLEM WELLPOSED IN THE SENSE OF HADAMARD FOR AN NONLINEAR BEAM EQUATION - Luyo Sánchez, José (2005)
We consider a dynamical system which is a modelfor nonlinear vibrations of an uniform prismatic beam of length L, taking into account the inline accelerations terms.We show that (he problem is wellposed in the sense of Hadamardfor strong solutions.